Osr1 Interacts Synergistically with Wt1 to Regulate Kidney Organogenesis. - Jingyue Xu; Han Liu; Ok Hee Chai; Yu Lan; Rulang Jiang (PLoS ONE)
Renal hypoplasia is a common cause of pediatric renal failure and several adult-onset diseases. Recent studies have associated a variant of the OSR1 gene with reduction of newborn kidney size and function in heterozygotes and neonatal lethality with kidney defects in homozygotes. How OSR1 regulates kidney development and nephron endowment is not well understood, however. In this study, by using the recently developed CRISPR genome editing technology, we genetically labeled the endogenous Osr1 protein and show that Osr1 interacts with Wt1 in the developing kidney. Whereas mice heterozygous for either an Osr1 or Wt1 null allele have normal kidneys at birth, most mice heterozygous for both Osr1 and Wt1 exhibit defects in metanephric kidney development, including unilateral or bilateral kidney agenesis or hypoplasia. The developmental defects in the Osr1+/-Wt1+/- mouse embryos were detected as early as E10.5, during specification of the metanephric mesenchyme, with the Osr1+/-Wt1+/- mouse embryos exhibiting significantly reduced Pax2-positive and Six2-positive nephron progenitor cells. Moreover, expression of Gdnf, the major nephrogenic signal for inducing ureteric bud outgrowth, was significantly reduced in the metanephric mesenchyme in Osr1+/-Wt1+/- embryos in comparison with the Osr1+/- or Wt1+/- littermates. By E11.5, as the ureteric buds invade the metanephric mesenchyme and initiate branching morphogenesis, kidney morphogenesis was significantly impaired in the Osr1+/-Wt1+/- embryos in comparison with the Osr1+/- or Wt1+/- embryos. These results indicate that Osr1 and Wt1 act synergistically to regulate nephron endowment by controlling metanephric mesenchyme specification during early nephrogenesis.